2017
DOI: 10.1371/journal.pone.0183509
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome in ADHD and its relation to neural reward anticipation

Abstract: BackgroundMicroorganisms in the human intestine (i.e. the gut microbiome) have an increasingly recognized impact on human health, including brain functioning. Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder associated with abnormalities in dopamine neurotransmission and deficits in reward processing and its underlying neuro-circuitry including the ventral striatum. The microbiome might contribute to ADHD etiology via the gut-brain axis. In this pilot study, we investigated pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
318
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(360 citation statements)
references
References 46 publications
17
318
3
1
Order By: Relevance
“…The gut microbiome, specifically, has also been an object of study in the context of ASD, with the levels of certain bacteria being significantly higher or lower in autistic children compared to controls (Adams et al 2011;Parracho et al 2005). Similar results were reported for attention deficit hyperactivity disorder (ADHD) as well (Aarts et al 2017). Interestingly, one study reported a genetic risk factor specific to a comorbid diagnosis of ASD and gastrointestinal dysfunction (Campbell et al 2009).…”
Section: Introductionmentioning
confidence: 65%
“…The gut microbiome, specifically, has also been an object of study in the context of ASD, with the levels of certain bacteria being significantly higher or lower in autistic children compared to controls (Adams et al 2011;Parracho et al 2005). Similar results were reported for attention deficit hyperactivity disorder (ADHD) as well (Aarts et al 2017). Interestingly, one study reported a genetic risk factor specific to a comorbid diagnosis of ASD and gastrointestinal dysfunction (Campbell et al 2009).…”
Section: Introductionmentioning
confidence: 65%
“…In addition, when patients with irritable bowel syndrome viewed negative emotional stimuli, treatment with probiotic Bifidobacterium longum NCC3001 (vs. placebo) reduced depression scores and altered brain activity in several brain regions, including amygdala and fronto-limbic regions (Pinto-Sanchez et al, 2017). Gut microbiota has also been related to ventral striatum responses to reward anticipation in a sample of adolescent ADHD patients (Aarts et al, 2017). Finally, in a group of healthy women, cluster analysis showed two groups (interestingly, higher Prevotella and higher Bacteroides), which could be differentiated by their brain morphometry characteristics (Tillisch et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies, 47,52,54,57 all investigating ASD, received a score of eight (high), due to matching cases and controls on other variables than age alone. Conversely, four studies (three investigating ASD and one investigating ADHD) 49,51,64,65 received a score of six (moderate), due to inadequate description of samples, 64 controls represented by children undergoing surgery and thus not being representative community controls, 49 or controls being older than ASD or ADHD cases (tables 3 and 4). 51,65 The remaining studies all received a score of seven (moderate).…”
Section: Study Selectionmentioning
confidence: 99%